2019
DOI: 10.1097/01.aoa.0000557694.16118.2d
|View full text |Cite
|
Sign up to set email alerts
|

Management of Anesthesia and Delivery in Women With Chiari I Malformations

Abstract: (Obstet Gynecol. 2018;132:1180–1184) A type I Chiari malformation, which is the most common type of Chiari malformation (0.6% prevalence), is defined as descent of the cerebellar tonsils below the foramen magnum by >5 mm. While most patients with this congenital malformation are asymptomatic, 30% can experience symptoms, ranging from headaches exacerbated by cough to more severe effects, such as confusion, deconjugate gaze, and papilledema as a result of increased intracranial pressure. Subsequent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…The retrospective case series identified that for those who are asymptomatic or manifest headache only as sequelae of their Chiari malformation, decision regarding mode of delivery should be based on obstetric considerations alone; whereas those manifesting papilloedema or hydrocephalus should be considered high risk for both vaginal delivery and neuroaxial block. 9 In practice, antepartum diagnosis of a Chiari malformation has been shown to influence both mode of delivery and woman's options of intrapartum analgesia, even when serious maternal morbidity rates with vaginal delivery or neuroaxial block remained comparable to normal controls and women who received the diagnosis postpartum. 10 The woman discussed here is a typical example of a parturient who was unaware of having a Chiari malformation and whose antenatal and intrapartum course were not adversely affected.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The retrospective case series identified that for those who are asymptomatic or manifest headache only as sequelae of their Chiari malformation, decision regarding mode of delivery should be based on obstetric considerations alone; whereas those manifesting papilloedema or hydrocephalus should be considered high risk for both vaginal delivery and neuroaxial block. 9 In practice, antepartum diagnosis of a Chiari malformation has been shown to influence both mode of delivery and woman's options of intrapartum analgesia, even when serious maternal morbidity rates with vaginal delivery or neuroaxial block remained comparable to normal controls and women who received the diagnosis postpartum. 10 The woman discussed here is a typical example of a parturient who was unaware of having a Chiari malformation and whose antenatal and intrapartum course were not adversely affected.…”
Section: Discussionmentioning
confidence: 99%
“…Neuroaxial block is both a safe and viable anaesthetic option for women with Chiari I malformation during labour; with no worsening neurological symptoms, 79 nor a higher incidence of anaesthetic complications such as postdural puncture headache following delivery. 7…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neuraxial anesthesia was administered to 62 of the deliveries without adverse effect. 15 The study concluded that in women with Chiari malformation type I who had no signs or symptoms of increased intracranial pressure, neuraxial anesthesia can safely be administered. A number of smaller studies also support the safety of spinal and epidural anesthesia in women with Chiari malformation type I.…”
Section: Chiari Malformationmentioning
confidence: 99%
“…It has been well established that neuraxial anesthesia poses no risk to women with decompressed Chiari malformation type I. 15 In 2017, a retrospective review was carried out for 97 deliveries of women with untreated Chiari malformation type I over a 5-year period. Neuraxial anesthesia was administered to 62 of the deliveries without adverse effect.…”
Section: Chiari Malformationmentioning
confidence: 99%